2006
DOI: 10.1007/s00125-006-0200-0
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of abnormal glucose homeostasis secondary to decreased insulin secretion in individuals with hereditary haemochromatosis

Abstract: Aims/hypothesis: The prevalence and mechanisms of diabetes in hereditary haemochromatosis are not known. We therefore measured glucose tolerance, insulin secretory capacity and insulin sensitivity in adults with haemochromatosis.Subjects and methods: Subjects recruited from referrals to a haemochromatosis clinic underwent OGTT and frequently sampled IVGTT. A chart review of former clinic patients was also performed. Results: The prevalence of diabetes (23%) and IGT (30%) was increased in haemochromatosis compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
135
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(144 citation statements)
references
References 43 publications
7
135
1
1
Order By: Relevance
“…In the same study, six haemochromatosis patients with diabetes had more markedly reduced AIRg, but, in addition, had decreased Si. Thus, all of the findings of Hramiak et al were consistent with those reported by McClain et al in the current issue [5]. Apparently conflicting results, however, were obtained in two earlier studies, in which non-diabetic haemochromatosis patients were found by OGTT or IVGTT to have persistent hyperinsulinaemia with normal or elevated serum glucose [8,9].…”
supporting
confidence: 88%
See 3 more Smart Citations
“…In the same study, six haemochromatosis patients with diabetes had more markedly reduced AIRg, but, in addition, had decreased Si. Thus, all of the findings of Hramiak et al were consistent with those reported by McClain et al in the current issue [5]. Apparently conflicting results, however, were obtained in two earlier studies, in which non-diabetic haemochromatosis patients were found by OGTT or IVGTT to have persistent hyperinsulinaemia with normal or elevated serum glucose [8,9].…”
supporting
confidence: 88%
“…The current work by McClain et al [5] clearly shows that reduced insulin secretory responses can be an early component of impaired glucose tolerance in haemochromatosis. Their findings that insulin sensitivity may actually be increased in this setting are interesting and are supported by their animal studies.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Patients with HH cannot respond with increased insulin secretion because of the primary impairment of b-cells. Insulin-secretory abnormalities improve with phlebotomy in this context (63).…”
Section: Iron and B-cell Relationshipsmentioning
confidence: 89%